La frase scissa nell’insegnamento dell’italiano per gli studenti di scienze umanistiche - Danijela Djorović (Scripta Manent, 2015)
The paper focuses on cleft sentences used in Italian academic texts and their reception by Humanities students learning Italian for academic purposes. Due to their complex form and usage, cleft sentences can be or become an obstacle to understanding and interpreting humanities academic texts written in Italian. The results of an action research carried out in a group of students of History and History of Art suggest that in order to teach students to notice and understand this particular syntactic construction, we need to offer a more explicit instruction and give our students a chance to explore the forms and usage of cleft sentences in larger authentic texts. The results of this study indicate that by encouraging students to work more actively on analyzing humanities texts, extracting examples of cleft sentences, studying and discussing them in groups and in plenum, we raise their awareness of the structure as well as their motivation to study. By gaining a better command of this structure students are more likely to read and comprehend texts of their expertise more accurately.